2013
DOI: 10.1638/2012-0249r1.1
|View full text |Cite
|
Sign up to set email alerts
|

PHYSIOLOGIC EFFECTS OF THREE DIFFERENT PROTOCOLS OF ISOFLURANE ANESTHESIA IN CAPTIVE BROWN BROCKET DEER (MAZAMA GOUAZOUBIRA)

Abstract: This study evaluates the cardiorespiratory and physiologic effects of three different protocols of chemical restraint using isoflurane in captive brown brocket deer (Mazama gouazoubira). Six adult deer, two males and four females, aged 3-6 yr old and weighing 16.3 +/- 1.5 kg (mean +/- SD), were used. The deer were physically restrained and anesthetized using one of three protocols: protocol 1 (P1), anesthesia was induced directly with isoflurane using a facemask and maintained for 1 hr with isoflurane delivere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Circulatory and respiratory inhibitions are common predictable adverse effects of general anesthesia using either inhalational or intravenous anesthetic agents. [61][62][63] Small animal models exposed to anesthetic agents need to have vital signs monitored and their normal physiological status maintained. 64 In animal models for anesthesia-induced developmental neurotoxicity, a range of measures have been designated to intensively monitor physiological parameters, including vital signs, blood oxygenation levels, and homeostasis, to assess if any alterations, including hypoxia or hypotension, occur during anesthetic exposure.…”
Section: Monitoring and Maintaining Of Physiological Statusmentioning
confidence: 99%
“…Circulatory and respiratory inhibitions are common predictable adverse effects of general anesthesia using either inhalational or intravenous anesthetic agents. [61][62][63] Small animal models exposed to anesthetic agents need to have vital signs monitored and their normal physiological status maintained. 64 In animal models for anesthesia-induced developmental neurotoxicity, a range of measures have been designated to intensively monitor physiological parameters, including vital signs, blood oxygenation levels, and homeostasis, to assess if any alterations, including hypoxia or hypotension, occur during anesthetic exposure.…”
Section: Monitoring and Maintaining Of Physiological Statusmentioning
confidence: 99%
“…In addition, ambient temperature at the moment of general anaesthesia and surgical intervention was characteristic of winter conditions, which has been associated with lower dose requirements compared to higher ambient temperature conditions. 7,8 Moreover, butorphanol was chosen among other opioid drugs due to its short duration of action and mild sedative and analgesic effects, 13,14,[19][20][21][22][23][24][25][26][27][28][29][31][32][33] which allowed the animal to become recumbent and to prepare the surgical area without deep sedation nor cardiovascular depression. Several publications have shown that deer can be prone to hypoxaemia, especially when sedated with α2-adrenoreceptor agonists 5,22,34,35 ; for that reason, pre-oxygenation was maintained during the duration of the pre-operative period.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18] Nevertheless, while these drug combinations have been reported more often during field anaesthesia, procedures that require longer anaesthesia duration demand a constant control of anaesthetic plane, which can be accomplished with inhalant anaesthetic agents. [19][20][21][22] To the authors' knowledge, the selection of the anaesthetic protocol of wild ungulates undergoing invasive procedures, such as an abdominal surgery, is poorly described in the literature. For this reason, here we report the anaesthetic management in a reindeer with jejuno-jejunal intussusception undergoing exploratory laparotomy and jejuno-jejuno anastomosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regurgitation is common in anaesthetised ruminants. Although not published in reindeer, it has been described in Tibetan yak, Shiras moose and brown brocket deer 4–6. Active regurgitation due to oesophageal contraction occurs under light planes of anaesthesia, while progressive abolishment of oesophageal muscle tone permits passive regurgitation under deep planes 7 8.…”
Section: Discussionmentioning
confidence: 99%